Tinjauan Literatur Investigasi Keselamatan ATS : Analisis Kecelakaan dan Insiden Pesawat Udara - Nurul Fadhilah Basri; Elfi Amir; Rany Adiliawijaya Putriekapuja (CV. ALIM'SPUBLISHING, 2026)
Aviation safety is a top priority in the global aviation industry, particularly concerning Air Traffic Services (ATS) which plays a critical role in preventing and investigating aircraft accidents and incidents. This literature review aims to analyze and synthesize findings from previous research on ATS Safety investigations, focusing on aircraft accidents and incidents during the period 2015-2024. The method employed is a narrative literature review using a targeted search strategy, drawing on relevant peer-reviewed journal articles, academic books, and official documents related to ATS Safety investigation. Inclusion criteria encompass peer-reviewed journal articles, official investigation reports from ICAO, KNKT, FAA, IATA, and Eurocontrol, as well as relevant case studies. A total of 28 sources were identified through a targeted search strategy, all of which met the inclusion criteria and were analyzed in depth. Review results indicate that human factors consistently emerge as the most frequently discussed contributor to ATS-related aviation accidents and incidents, followed by technical and environmental factors. Findings also suggest that effective implementation of Safety Management Systems (SMS), continuous training for ATS personnel, and the use of modern surveillance technology can significantly reduce accident and incident risks. This study concludes the necessity of a proactive approach in ATS Safety management, including the development of a strong safety culture in every air traffic service unit.